2021
DOI: 10.1007/s10653-021-00936-9
|View full text |Cite
|
Sign up to set email alerts
|

Multiple geochemical factors may cause iodine and selenium deficiency in Gilgit-Baltistan, Pakistan

Abstract: Deficiencies of the micronutrients iodine and selenium are particularly prevalent where populations consume local agricultural produce grown on soils with low iodine and selenium availability. This study focussed on such an area, Gilgit-Baltistan in Pakistan, through a geochemical survey of iodine and selenium fractionation and speciation in irrigation water and arable soil. Iodine and selenium concentrations in water ranged from 0.01–1.79 µg L−1 to 0.016–2.09 µg L−1, respectively, which are smaller than level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 118 publications
(220 reference statements)
0
2
0
Order By: Relevance
“…Overcollection by pharmaceutical organizations and the growing population have contributed to the % of method of uses increased use of these plants, endangering their existence. Additionally, natural and human-induced factors like climate change, overgrazing (Ahmad et al, 2021), and unsustainable harvesting practices pose threats to the medicinal plants in the study area (Rambey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Overcollection by pharmaceutical organizations and the growing population have contributed to the % of method of uses increased use of these plants, endangering their existence. Additionally, natural and human-induced factors like climate change, overgrazing (Ahmad et al, 2021), and unsustainable harvesting practices pose threats to the medicinal plants in the study area (Rambey et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…It has been found that iodine deficiency is common for terrains where the population consumes local agricultural products grown on soils poor in iodine. [ 51 , 52 ]. Formal studies to determine the dietary intake of iodine in western Kazakhstan have not been performed yet.…”
Section: Discussionmentioning
confidence: 99%